Pengembangan Lembar Kerja Peserta Didik Berbasis Project Based Learning Kelas V SD Negeri 36 Pontianak Kota - Elyasmad Elyasmad; Suparjan Suparjan; Rio Pranata; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study aims to produce a student worksheet product based on Project Based Learning in class V SDN 36 Pontianak City that is feasible. The research method used is research and development (RnD) by adapting the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data sources of this study were the validation results of three material expert validators, a design expert linguist, the results of teacher and student practicality questionnaires, and the results of student worksheet trials. The data collection techniques for this research are validator validation questionnaires, practicality questionnaires, test questions for students, and documentation on the LKPD used by teachers. The results showed that the process of developing LKPD based on Project Based Learning in class V at SDN 36 Pontianak City, was carried out only in three stages, namely the analysis stage, design, and development. LKPD validity, the average percentage from the learning aspect (material) is 4 with very valid criteria, from the design aspect it is 4 with very valid criteria, the language aspect it is 3.8 with very valid criteria. The practicality of using Project Based Learning-based worksheets by teachers is 92.5% with a very practical category, and the level of completeness in the first trial obtained an average percentage of completeness 91.67% with very good criteria and the second trial obtained an average percentage of completeness 92% with very good criteria.